1998
DOI: 10.1097/00005537-199804000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxidation As a Measure of Free Radical Injury in Otitis Media

Abstract: Free radical damage, as evidenced by lipoperoxidation, has previously been demonstrated to contribute to the inflammatory changes associated with acute otitis media. The present study was undertaken to evaluate whether lipoperoxidation continues to be present for a period of time after middle ear infection. Eighty-two 300- to 400-g guinea pigs were injected with Streptococcus pneumoniae in the left ear and sterile saline in the right ear as a control. Animals were examined and sacrificed on day 5, 10, 20, or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…Furthermore, when compared the AOM and AT groups, there was statistically significant difference between the groups (Table 1). Many investigators, both experimental [16][17][18][19][20] and human [21][22][23][24][25] studies have measured lipid peroxidation levels in AOM and acute or chronic tonsillitis. These studies also demonstrated that increased oxidative stress in the both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when compared the AOM and AT groups, there was statistically significant difference between the groups (Table 1). Many investigators, both experimental [16][17][18][19][20] and human [21][22][23][24][25] studies have measured lipid peroxidation levels in AOM and acute or chronic tonsillitis. These studies also demonstrated that increased oxidative stress in the both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical analysis of the mucosa has demonstrated elevated levels of LPO, which is an indication of FR‐mediated lipid damage after infection. 2,3 …”
Section: Discussionmentioning
confidence: 99%
“…In this model, FRs are hypothesized to be generated by both S. pneumoniae and neutrophils responding to infection. 2,3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Lipoperoxidation caused by free radicals may contribute to middle ear inflammation after acute infection. 9 …”
Section: Introductionmentioning
confidence: 99%